CORRELATION OF CREATIVITY AND INTELLECT ON THE EXAMPLE OF FILM PROJECTS MADE IN HONK KONG, LATVIA AND RUSSIA - Aparina , A. (EurasianUnionScientists, 2021)
The purpose of this article is to determine the connection between two terms – creativity and intellect, to identify which one can be influenced by another, to determine whether the influence of the IQ on the creation exists. As an example, the author describes the film project experience made in three countries.